Rethoric Of The Digital Image In The Literary Text Interactive - medjenah, Djmel (The Notebooks of the Algerian Poetics Laboratory Journal, 2025)
If we recognise that the imageis a text in its own right as a plastic or pictorial art, that it carries its own discourse, its own indicators and its own independent modes of reading, its combination with the digital or interactive literary text confronts us with a double discourse, which requires critical procedures capable of taking the different aspects into account. Interactive literature has tended to exploit static and moving digital images as aesthetic interfaces for texts, and they have become metaphors that indicate a new or additional rhetoric, since the studies that have dealt with interactive literature have considered it as a digital rhetoric with its own metaphorical characteristics and aesthetic impact.